2015
DOI: 10.1186/s12889-015-1674-9
|View full text |Cite
|
Sign up to set email alerts
|

Training Sri Lankan public health midwives on intimate partner violence: a pre- and post-intervention study

Abstract: BackgroundIn many developing countries, intimate partner violence (IPV) training is not available for health providers. As a pioneer among developing countries, in 2009, the Sri Lankan Ministry of Health trained a group of community health providers known as public health midwives (PHMs) on IPV. We evaluated that training program’s efficacy in improving PHMs’ identification and management of IPV sufferers in Kandy, Sri Lanka.MethodsWe conducted this study from August 2009 to September 2010. We used a self-admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
109
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(118 citation statements)
references
References 20 publications
2
109
0
6
Order By: Relevance
“…, Jayatilleke et al . ). A study of Turkish‐based postregistration emergency department nurses identified a lack of previous IPV education for all participants in the trial (Yildiz et al .…”
Section: Resultsmentioning
confidence: 97%
“…, Jayatilleke et al . ). A study of Turkish‐based postregistration emergency department nurses identified a lack of previous IPV education for all participants in the trial (Yildiz et al .…”
Section: Resultsmentioning
confidence: 97%
“…They described an increasing sense of confidence in routinely screening their clients, and related strategies for doing this safely. Jayatilleke et al (2015) reported that a DV training programme for public health midwives improved identification of and assistance for DV victims in Sri Lanka. They also suggested that the training programme had the potential to improve midwives' skills in preventing DV.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with these results, DV education should examine gender roles and the effects of traditional gender roles on attitudes towards DV. A study by Jayatilleke et al (2015) emphasized that gender roles were an integral part of DV training programmes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations